Airpnp: Auto- and Integrated Regulation of Polynucleotide Phosphorylase - Ciarán Condon (Journal of Bacteriology, 2015)
ABSTRACT The properties and expression of polynucleotide phosphorylase (PNPase), capable of both RNA degradation and polymerization, have been studied for 60 years. In this issue of the Journal of Bacteriology , Park et al. (H. Park, H. Yakhnin, M. Connolly, T. Romeo, and P. Babitzke, J Bacteriol 197:3751–3759, 2015, http://dx.doi.org/10.1128/JB.00721-15 ) write the latest chapter on the complex regulation of pnp gene expression involving CsrA. I describe how this new piece of the puzzle fits into the global scheme of PNPase autoregulation and how this is influenced by central carbon metabolism at both the posttranscriptional level and that of enzyme activity.